2006
DOI: 10.1590/s1516-35982006000600020
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de cálcio e granulometrias do calcário para frangas e seus efeitos sobre a produção e qualidade de ovos

Abstract: RESUMO -Realizou-se um experimento com o objetivo de avaliar os efeitos dos níveis nutricionais de cálcio e das granulometrias do calcário em rações para frangas nas fases de cria e recria sobre a produção de ovos. Utilizaram-se 600 poedeiras da linhagem Lohmann LSL, alimentadas nos períodos de cria e recria com rações experimentais suplementadas com fitase (500 FTU/kg) e calcário em granulometrias fina (DGM = 0,135 mm) e grossa (DGM = 0,899 mm) para atender os níveis de 0,60; 0,75; 0,90; 1,05 e 1,20% de Ca to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
2
10
1
Order By: Relevance
“…No significant effects (P>0.05) of calcium levels and limestone particle size or their interaction (calcium × size) were observed on the digestive tract proportion to the body weight of laying hens during production stage ( Table 7). The result is consistent with the findings of Geraldo et al (2006), who noted no significant effect of calcium and limestone texture on the digestive tract percentage of laying hens.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…No significant effects (P>0.05) of calcium levels and limestone particle size or their interaction (calcium × size) were observed on the digestive tract proportion to the body weight of laying hens during production stage ( Table 7). The result is consistent with the findings of Geraldo et al (2006), who noted no significant effect of calcium and limestone texture on the digestive tract percentage of laying hens.…”
Section: Resultssupporting
confidence: 92%
“…However, there was no significant effect (P>0.05) of limestone particle size, which contradicts, in part, the results described by Geraldo et al (2006), who found a positive residual effect of fine granulometry in phases of rearing and re-rearing of hens on the average egg production at the production stage. There was no effect (P>0.05) of calcium levels and particle size of limestone on the egg weight.…”
Section: Resultscontrasting
confidence: 84%
See 3 more Smart Citations